Metachronous colorectal cancer risks after extended or segmental resection in MLH1, MSH2, and MSH6 Lynch syndrome: multicentre study from the Prospective Lynch Syndrome Database - Zalevskaja, Kristina; Haupt, Saskia; Heuveline, Vincent; Knebel Doeberitz, Magnus von (The British journal of surgery, 2025)
The aim of this study was to prospectively evaluate the risk of metachronous CRC, stratified by gene and the extent of the resection in previous surgery, contributing to the ongoing discussion on surgical strategies for LS patients.